Balancing Robot Menggunakan Metode Kendali Proporsional Integral Derivatif - Rizka Bimarta; Agfianto Eko Putra; Andi Dharmawan (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2015)
Center of gravity’s inverted pendulum is located above its pivot point therefore inverted pendulum is unstable. Specific control is needed so that inverted pendulum stable which is by move the cart where the pendulum is mounted. Inverted pendulum application can be found in balancing robot. The purpose of this research is to design a system to control a two wheeled robot using the control system to balance it.The inputs are accelerometer to measure angular acceleration (m/s2) and gyroskop to measure angular velocity (rad/s). The output’s of accelerometer and gyroscope are fused by complementary filter algorithm method to get the actual angle. The actual angle is then compared to set point which is 0o. The differences between set point and actual angle are processed using Proportional Integral Derivative control method. The process of PID control is programmed using Arduino IDE which its result is fed to DC motors. The direction of DC motors are determined by two conditions, if actual angle less than zero then DC motors will spin backwards. Whereas if actual angle more than zero then DC motors will spin forward. The PID control’s constans value based on Ziegler-Nichols Oscillation tuning method are Kp=1.5, Ki=0.75, Kd=1.875 and complementary filter’s coefficient is a=0.96.